P-6 Advance care planning and goals of care designation: Health care provider perspectives. (1st September 2015) - Ogilvie, LN; Fassbender, K; Wasylenko, Eric; Holroyd-Leduc, J; Davison, S; Ghosh, S; Howlett, J; Simon, Jessica E
Abstract : Background: The Advance Care Planning (ACP) and Goals of Care Designation (GCD) policy provides guidance to health care providers (HCP) in Alberta on how to communicate verbally and document patients' and families' values and wishes using a medical order. Aim: To apply a knowledge translation framework, the Theoretical Domains Framework (TDF), to HCP perspectives on ACP and GCD in their clinical setting.  Methods: HCP (n = 542) including nurses (n = 331), doctors  (n = 94) and allied HCP (n = 117) working in the areas of renal failure, cardiac failure, oncology and seniors care responded to a web-based survey that was developed through consultation and pilot testing. Leaders in each clinical area distributed the survey through their networks. Results: Respondents agreed that ACP/GCD benefits patients with 85.43% rating benefit as 6 or 7 on the 7-point scale. The most common barrier was competing tasks and time constraints as 37.11% of HCP chose 6 or 7 when asked how much they impede ACP/GCD practice. Discussion: When mapped to the TDF these results indicate that the category "beliefs about consequences" is a facilitator to policy implementation. The category "memory, attention and decision processes" may include the greatest barriers. As represented on the COM-B model (capability, opportunity, and motivation) HCP are high on motivation but face barriers in the area of capabilities. Conclusion: Using a survey based on the TDF has allowed us to identify areas of priority for investment in behaviour change techniques to aid with uptake of ACP and GCD procedures.